PERBANDINGAN KOMPRES DINGIN DAN KOMPRES HANGAT TERHADAP PENURUNAN NYERI MENSTRUASI DI PONDOK PESANTREN KABUPATEN NGAWI: Universitas Kusuma Husada Surakarta - Willda Nurrafi; Wijayanti Wijayanti; Tresia Umarianti (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
ABSTRACT Background: Menstrual pain is something that occurs before and during menstruation which can interfere with activities. The prevalence of dysmenorrhea in Indonesia is 60-70% of women. Cause discomfort, interfere with daily activities, overcome pharmacological and non-pharmacological menstrual pain. Purpose: To compare the effectiveness of cold compresses and warm compresses to reduce menstrual pain. Methods: This study was a quasi-experimental. Samples were taken by purposive sampling technique with a total of 52 female students. Data collection used the NRS 0-10 observation sheet. Data analysis used the Wilcoxon Test and the Mann Whitney Test. Results: The average menstrual pain before and after being given a cold compress was (4.3) to (3.92). Whereas before and after the warm compress given was (3.69) to (1.92). Furthermore, the Wilcoxon test means that there is a difference between before and after the warm compress technique with a Sig. (0.000) and cold compresses with a value of Sig.(0.003). Because in the normality test there are data that are not normally distributed on the results of the difference test using the Mann Whitney test with the result (p = 0.000), there is a difference in the decrease in menstrual pain with warm compresses and cold compresses. Conclusion: warm compresses are more effective in reducing menstrual pain